1981
DOI: 10.1080/01411598108241319
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and light scattering spectroscopy of incommensurate phases in crystals

Abstract: Dielectric and light scattering spectroscopy are the most sensitive methods for the direct observation of low-frequency excitations in incommensurate phases. In several cases they have been successfully used for the observation of amplitudon and phason modqs. Whereas the amplitudon below the normal-incommensurate transition temperature behaves in a similar way to soft modes at common structural transitions, the phason represents a qualitatively new feature of incommensurate phases. All the corresponding experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 220 publications
0
30
0
Order By: Relevance
“…These experimental results correspond to the flexocoupling constants of the order of a few hundred volts 6 and customarily discussed in terms of the static bulk flexoelectric effect. At the same time, the upper bounds (17) and (18) suggest that so high values of the flexocoupling constants would have lead to the formation of the incommensurate phase in these materials. 15 Since no incommensurate phase been reported, either in BaTiO 3 or in SrTiO 3 , the high flexoelectric response in perovskite ceramics can hardly be due to the static bulk flexoelectric effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These experimental results correspond to the flexocoupling constants of the order of a few hundred volts 6 and customarily discussed in terms of the static bulk flexoelectric effect. At the same time, the upper bounds (17) and (18) suggest that so high values of the flexocoupling constants would have lead to the formation of the incommensurate phase in these materials. 15 Since no incommensurate phase been reported, either in BaTiO 3 or in SrTiO 3 , the high flexoelectric response in perovskite ceramics can hardly be due to the static bulk flexoelectric effect.…”
mentioning
confidence: 99%
“…17 While the inequalities obtained indicate the upper bounds for flexoelectric constants in materials where incommensurate phase does not form, they may also be used to understand materials where such phases indeed form. 8,18 …”
mentioning
confidence: 99%
“…For the latter, more information is needed, but it is clear that the space group is neither that reported for/3-nor that reported for a'-Sr2SiO4. modulated in the b direction, some with an approximately 2x period [(NH4)2BeF4 (Petzelt, 1981)] but most with an approximately 3 x period [Rb2ZnCL and Rb2ZnBr4 (Hogervorst & de ~/olff, 1982); K2ZnCI4 (Kucharczyk, Paciorek & Kalicifiska-Karut, 1981); K2SeO4 (Petzelt, 1981); etc.] -cf.…”
Section: Discussionmentioning
confidence: 99%
“…Already in 1970 [18], Axe et al pointed out that the phonon dispersion curves for the ferroelectric KTaO 3 suggest that mode coupling (which is, as presently known, due to flexoelectricity) can lead to the formation of the incommensurate state in perovskite ferroelectrics. In fact, a large number of ferroelectric materials are known to exhibit modulated phases [19][20][21]. Prior studies of incommensurate phases in ferroelectrics revealed the presence of one-dimensional modulations/stripe domain patterns.…”
Section: −1mentioning
confidence: 99%